An Analysis Of The Role Of Interest Rates On The Money Supply, Credit, And Their Implications For The Macroeconomy - Sindy Meilani; Sanusi Gazali Pane; Dinia Putri Ramadhani; Tasya Melinda Amran (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the role of interest rates as a monetary policy instrument in influencing the money supply and credit disbursement, as well as its implications for macroeconomic conditions. Conceptually, interest rates function as a monetary policy transmission mechanism that affects public behavior regarding consumption, investment, and savings. Fluctuations in interest rates impact borrowing costs, which subsequently influence credit demand and the volume of money circulating within the economy. The interaction between interest rates, money supply, and credit is believed to play a pivotal role in determining price stability, economic growth, and inflation rates. This research adopts a macroeconomic and monetary theoretical approach to explain the causal relationship between these variables, providing a comprehensive overview of the effectiveness of interest rate policies in maintaining economic stability and growth. The findings are expected to demonstrate that interest rates exert a significant influence on the money supply and credit allocation. A reduction in interest rates is anticipated to stimulate an increase in credit and money supply, thereby having a positive impact on economic activity and output growth. Conversely, an increase in interest rates is expected to curb inflation through the regulation of credit and liquidity. Furthermore, this study is intended to provide a clearer understanding of the role of monetary policy in preserving macroeconomic stability and to serve as a reference for policymakers in formulating inflation control strategies and promoting sustainable economic growth.